Immigration and Income Inequality: A Comparative Study of Denmark and Germany, 1984-2003 - Deding, Mette; Hussain, M Azhar; Jakobsen, Vibeke; Brodmann, Stefanie (Journal of Income Distribution®, 2009)
During the last two decades most Western countries have experienced increased net immigration as well as increased income inequality. This article analyzes the effects on income inequality of an increased number of immigrants in Denmark and Germany for the 20- year period 1984-2003 and how the impact of the increased number of immigrants differs between the two countries. We find higher inequality for immigrants than natives in Denmark but vice versa for Germany. Over the period 1984-2003, this particular inequality gap has narrowed in both countries. At the same time, the contribution of immigrants to overall inequality has increased, primarily caused by increased between-group inequality. The share of immigrants in the population is more important for the change in overall inequality in Denmark than in Germany, while the opposite is the case for inequality among immigrants.